Glycation of Nail Proteins as a Risk Factor for Onychomycosis. Comment on Gupta et al. Diabetic Foot and Fungal Infections: Etiology and Management from a Dermatologic Perspective. J. Fungi 2024, 10, 577 - Terenzio Cosio; Isabel Valsecchi; Roberta Gaziano; Elena Campione; Françoise Botterel (Journal of Fungi)
We read the review by Gupta et al [...]